2020
DOI: 10.3390/f11090901
|View full text |Cite
|
Sign up to set email alerts
|

Stand-Level Transpiration Increases after Eastern Redcedar (Juniperus virginiana L.) Encroachment into the Midstory of Oak Forests

Abstract: Eastern redcedar (Juniperus virginiana L., redcedar) encroachment is transitioning the oak-dominated Cross-Timbers of the southern Great Plain of the USA into mixed-species forests. However, it remains unknown how the re-assemblage of tree species in a semiarid to sub-humid climate affects species-specific water use and competition, and ultimately the ecosystem-level water budget. We selected three sites representative of oak, redcedar, and oak and redcedar mixed stands with a similar total basal area (BA) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…2019; Torquato et al . 2020). However, there is evidence that under increasing drought stress, species interactions can shift from a positive to a negative interaction because of increasing niche overlap (Rodríguez‐Robles et al .…”
Section: Increasing Drought Stress Has Adverse Effects On Tree Resist...mentioning
confidence: 99%
“…2019; Torquato et al . 2020). However, there is evidence that under increasing drought stress, species interactions can shift from a positive to a negative interaction because of increasing niche overlap (Rodríguez‐Robles et al .…”
Section: Increasing Drought Stress Has Adverse Effects On Tree Resist...mentioning
confidence: 99%
“…Norris et al (2001) found that eastern redcedar stands in the Great Plains ranged from 7 Mg ha −1 year −1 in a 70 year old stand to over 10 Mg ha −1 year −1 for a 35 year old stand from an area with precipitation (average 835 mm per year) similar to our site. Based on aerial imagery and coring of several trees (Nunes Biral et al, 2019; Torquato, Will, et al, 2020), the eastern redcedar in our study were approximately 40 years old. The standing biomass of our eastern redcedar stands (61 and 112 Mg ha −1 ) also was lower than estimates from Norris et al (2001) where standing biomass ranged from 114 to 211 Mg ha −1 .…”
Section: Discussionmentioning
confidence: 81%
“…Post oak is a slow growing species and its growth is sensitive to low precipitation (Stahle & Hehr, 1984). A subset of post oaks measured at our site averaged 95 years old (Torquato, Will, et al, 2020). Another factor that impacted the productivity of the oak watersheds was the encroachment of eastern redcedar into the forest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, runoff dynamics were altered: whereas runoff from grasslands was typically generated as saturation overland flow, that from the juniper-encroached sites was generated as infiltration-excess overland flow (Qiao et al, 2017). These ecohydrological changes are being driven largely by higher transpiration and interception losses in the juniper woodlands (Caterina et al, 2014;Wang et al, 2018b;Torquato et al, 2020). Modeling exercises and historical streamflow records suggest that these smaller-scale changes will result in reduced streamflows at larger scales (Zou et al, 2016;Starks and Moriasi, 2017).…”
Section: Case Studies Along a Climate Gradientmentioning
confidence: 99%